2008
DOI: 10.1007/s11802-008-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on hemolymph osmotic pressure, sodium concentration and Na+-K+-ATPase activity of gill of Chinese crab, Eriocheir sinensis

Abstract: The effects of salinity on hemolymph osmotic pressure, Na + concentration and Na + -K + -ATPase activity of gill of Chinese crab Eriocheir sinensis were studied. The results showed that hemolymph osmotic pressure and Na + concentration increased significantly (P<0.05), and the Na + -K + -ATPase activity of gills decreased significantly (P<0.05) when salinity increased from 0 to 16. The hemolymph osmotic pressure and Na + concentration in each treatment group rose remarkably at 0.125 d or 0.25 d, while the Na +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…After 24 h, the Na + -K + -ATPase activity in red P. fucata increased significantly with the increase of salinity, which is consistent with the changing trend of osmotic pressure. Liu et al (2008) found that Na + -K + -ATPase activity of Eriocheir sinensis is negatively correlated with salinity, which is different from the results of our study, indicating that osmotic regulation of P. fucata is not completely implemented by Na + -K + -ATPase in the gill tissue. It is possible that in a short time of salinity stress, biogenic amines (dopamine and serotonin) could stimulate phosphorylation of the enzyme in the gills including the Na + -K + -ATPase, and then ATPases could adjust the ion concentration both in vivo and in vitro and make the osmotic pressure of hemolymph attain a balance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After 24 h, the Na + -K + -ATPase activity in red P. fucata increased significantly with the increase of salinity, which is consistent with the changing trend of osmotic pressure. Liu et al (2008) found that Na + -K + -ATPase activity of Eriocheir sinensis is negatively correlated with salinity, which is different from the results of our study, indicating that osmotic regulation of P. fucata is not completely implemented by Na + -K + -ATPase in the gill tissue. It is possible that in a short time of salinity stress, biogenic amines (dopamine and serotonin) could stimulate phosphorylation of the enzyme in the gills including the Na + -K + -ATPase, and then ATPases could adjust the ion concentration both in vivo and in vitro and make the osmotic pressure of hemolymph attain a balance.…”
Section: Discussioncontrasting
confidence: 99%
“…The metabolic activities of H. cracherodii and H. rufescens under high-salinity stress were swiftly and significantly impacted within 10 min, and began to resume in 6-8 h (Berger and Kharazova, 1997). Liu et al (2008) found that the hemolymph osmotic pressure of C. japonica tended to be stable within 0.5 days in each treatment group with a sudden change of salinity. In this study, the osmotic pressure of P. fucata with two shell colors in the experimental group was significantly different from that of the control group at 24 h, which may be due to the large range of salinity changes in the experimental group, leading to a wider range of hemolytic osmotic pressure changes, thus increasing the adjustment and recovery time of P. fucata osmotic pressure.…”
Section: Discussionmentioning
confidence: 86%
“…Little is known about primary chemical messengers involved in the regulation of digestive enzyme activities in the hepatopancreas of decapod crustaceans. Dopamine (DA) an important neurotransmitter and neurohormone in crustaceans (Fingerman et al 1994;Clark et al 2008;Christie 2011) is involved in the regulation of various processes, metabolic pathways, and enzyme activities (Mo et al 1998;Morris 2001;Lucu and Towle 2003;Halperin et al 2004;Pinoni and López Mañanes 2004;Cheng et al 2005;Lorenzon et al 2005;Chiu et al 2006;Genovese et al 2006;Hsieh et al 2006;Yeh et al 2006;Chang et al 2007;Liu et al 2008;Avramov et al 2013;Swetha et al 2014;Pan et al 2014). Various chemical messengers, such as biogenic amines including DA have been detected in the hepatopancreas, which appears also to be an important endocrine organ (Huang et al 2005).…”
Section: L-alaninementioning
confidence: 99%
“…So far, the effects of salinity on osmotic pressure (Lu et al, 2011), immune stress (Wang et al, 2012), reproductive development (Long et al, 2017) and some physiological and biochemical indicators, such as proteins (Wang & Xu, 2003) and amino acids (Wang et al, 2018), have been studied. In ion transport, Na + , K + , Cl − and enzymes related to Na + , K + , Cl − transport, such as Na + -K + -ATPase, have been studied (Feng et al, 2013;Liu et al, 2008Liu et al, , 2018 .…”
Section: Introductionmentioning
confidence: 99%